Associations between default‐mode functional connectivity and distress, cardiovascular and metabolic risks and cognition in middle aged and older adults. (20th December 2022) - Rashid, Barnaly; Glasser, Matthew F.; Nichols, Thomas; Van Essen, David; Juttukonda, Meher R; Schwab, Nadine A; Yacoub, Essa; Lovely, Allison; Terpstra, Melissa; Harms, Michael P; Bookheimer, Susan Y.; Ances, Beau M; et al.
Abstract: Background: "Stress" and cardiovascular and metabolic (CVM) conditions are frequently related and affect brain function and increase risk for neurocognitive disorders in aging. The mechanisms by which these occur are unclear. This study investigates how indices of psychological distress and CVM relate to functional connectivity (FC) of the default‐mode network (DMN) and cognition in generally healthy middle‐aged and older adults. Method: Structural, Resting‐state fMRI, and fieldmap scans were collected in a large sample of 930 healthy volunteers aged 36 to 90+ years old (mean ± SD: 61.6 ± 16 years; female= 55.6%) from the Human Connectome Project in Aging (HCP‐A) study. Data were preprocessed using the currently recommended HCP pipelines, including precise spatial preprocessing, multi‐modal cross‐subject alignment, and selective temporal denoising. FC values were computed using full correlation with FSLNets amongst the neocortical brain areas of the HCP's multi‐modal parcellation and standard FreeSurfer subcortical structures and converted to z‐scores with the Fisher transform. A psychological distress index (PDI) was composed from standard measures of external and social stressors, personality and mental health factors. A CVM index (CVMI) was composed from common physiological and laboratory measures (e.g., blood pressure, lipids, C‐reactive protein), and cognitive functioning was summarized with a multi‐domain cognition composite index (CCI) with standard measures of general cognition, memory, processing speed, and executive functioning. Using linear regression models controlling for age, associations between DMN FC and PDI, CVMI and CCI were evaluated. Result: Figure 1 highlights the associations (uncorrected, p<0.05) between DMN FC and (a) PDI, (b) CVMI and (c) CCI. The overlapping associations in Figure 1(d) suggest that there might be a shared mechanism through which PDI and CVMI impact DMN FC and cognition. Although associations based on PDI were relatively weak, it is possible that effects may be linked to specific elements or subgroups, and this will be explored in future work. Conclusion: Our findings indicate that psychological distress and CVM health affect the integrity of DMN connectivity, and that these effects show regional overlaps with the associations between DMN connectivity and cognition.